2015
DOI: 10.1016/j.adolescence.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Being bullied and feeling ashamed: Implications for eating psychopathology and depression in adolescent girls

Abstract: The current study examined the associations between peer victimization, body image shame, self-criticism, self-reassurance, depressive symptoms and eating psychopathology in 609 female adolescents.Correlational analyses showed that being the victim of bullying was positively associated with body image shame, self-criticism, with low self-reassurance, depressive symptoms and eating psychopathology. A path analysis indicated that victimization experiences were associated with increased depressive symptoms partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 69 publications
(138 reference statements)
4
34
0
3
Order By: Relevance
“…Also, body image-related victimization experiences were positively linked with depressive, anxiety and stress symptoms, current body image shame and eating psychopathology, namely binge eating These findings add to previous evidence demonstrating the role of these experiences on disordered eating symptomatology (e.g., Menzel et al 2010) and on the individual self-evaluation and psychological and interpersonal functioning (Duarte, Pinto-Gouveia, and Rodrigues 2015;Haines et al 2006;Lunde et al 2006;Matos et al 2015;Menzel et al 2010;Pinto-Gouveia et al 2014). …”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Also, body image-related victimization experiences were positively linked with depressive, anxiety and stress symptoms, current body image shame and eating psychopathology, namely binge eating These findings add to previous evidence demonstrating the role of these experiences on disordered eating symptomatology (e.g., Menzel et al 2010) and on the individual self-evaluation and psychological and interpersonal functioning (Duarte, Pinto-Gouveia, and Rodrigues 2015;Haines et al 2006;Lunde et al 2006;Matos et al 2015;Menzel et al 2010;Pinto-Gouveia et al 2014). …”
Section: Discussionsupporting
confidence: 68%
“…Moreover, the BIVES was positively associated with current levels of self-criticism, (Gilbert et al 2004), which has been associated with poor mental health indicators, namely eating psychopathology Duarte, Pinto-Gouveia, and Rodrigues 2015;PintoGouveia, Ferreira, and Duarte 2014). Also, body image-related victimization experiences were positively linked with depressive, anxiety and stress symptoms, current body image shame and eating psychopathology, namely binge eating These findings add to previous evidence demonstrating the role of these experiences on disordered eating symptomatology (e.g., Menzel et al 2010) and on the individual self-evaluation and psychological and interpersonal functioning (Duarte, Pinto-Gouveia, and Rodrigues 2015;Haines et al 2006;Lunde et al 2006;Matos et al 2015;Menzel et al 2010;Pinto-Gouveia et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, there is evidence suggesting that bullying is associated with adolescents' negative perceptions that their body is the target of criticism from others (Lunde, Frisén, & Hwang, 2006). A recent study conducted with adolescent girls revealed that the extent to which bullying is associated with eating psychopathology symptoms is influenced by how bullying becomes linked to body image shame and self-criticism (Duarte, Pinto-Gouveia, & Rodrigues, 2015). Moreover, bullying experiences may have lasting effects on body image and eating-related difficulties.…”
Section: Introductionmentioning
confidence: 99%